The Implementation of Elementary School English Teacher With Non-English Educational Background Towards Pedagogical Content Knowledge - Puspitawati, Eka Ulyana; Utami, IGA Lokita Purnamika; Suprianti, GAP; Riastini, Putu Nanci (Interference: Journal of Language, Literature, and Linguistics, 2023)
Abstract. At elementary schools in Bali, there were English teachers who taught English but did not have an English education background, included pedagogical content knowledge. Therefore, the aim of this research are to describe how are the teacher’s perception and implementation of pedagogical content knowledge in English learning for young learners and to compare the result of the perception and implementation by elementary school English teacher who do not have English educational background in Denpasar. The subject of this research was three English teachers in three different elementary schools in Denpasar with a non-educational English background that were selected using a convenience sampling technique. Mix method which was dominant in using qualitative was the research design. Questionnaire, observation sheet, and interview guide was the instrument used in this study. The result of this study showed that teachers’ perception towards pedagogical content knowledge was high, but the implementation was very low. The comparison between teacher’s perception and implementation towards pedagogical content knowledge showed that the teacher’s had lack of consistency. Therefore, learning activities become less effective. In conclusion, the teachers need to improve the implementation of pedagogical content knowledge first before teaching in the class. Keywords: PCK, perception, implementation, young learners, English teacher